Gold Decorated Hydroxyapatite–CeO2 Enabled Surface Frustrated Lewis Pairs for CO Oxidation. Issue 11 (18th September 2022) - Guo, Jiuli; Song, Rui; Li, Zehao; Pan, Donghui; Xie, Haijiao; Ba, Yantao; Xie, Ming; Fan, Shijiao; Yang, Xuedong; Zhang, Haibo; Yu, Huanhuan; Zhang, Shoumin; et al.
Abstract : The activation of molecular oxygen (O2 ) holds the fundamental step for reaction mechanism of carbon monoxide oxidation. Surface frustrated Lewis pairs (SFLPs) with sterically hindered Lewis acid–base pairs are proven to activate small molecules, such as hydrogen. However, the activation of molecular O2 on SFLPs remains unexplored. Herein, the construction of SFLPs in Au decorated hydroxyapatite (HAP)–CeO2 heterojunction is reported. The coordinately unsaturated Lewis acidic Ce 3+ and the Lewis basic OH − group in HAP enable the activation of O2 molecules to O 2 − –Ce 3+ species for carbon monoxide (CO) oxidation. The active site is identified based on the comprehensive in situ electron paramagnetic resonance, in situ diffuse reflectance infrared Fourier transform spectroscopy, X‐Ray absorption spectroscopy, and theoretical simulation. The results provide a new strategy to construct SFLPs sites for O2 molecule activation and the subsequent CO oxidation. Abstract : Well‐designed in situ characterizations and density functional theory calculations provide insight into a new surface frustrated Lewis pair (SFLP) in Au decorated hydroxyapatite (HAP)–CeO2 heterojunction. The O 2 − –Ce 3+ intermediate is identified and generated by the activation of O2 molecules on the SFLPs (Ce 3+ –OH pairs) for CO oxidation.